2016
DOI: 10.1016/j.cortex.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-tensor imaging of major white matter tracts and their role in language processing in aphasia

Abstract: A growing literature is pointing towards the importance of white matter tracts in understanding the neural mechanisms of language processing, and determining the nature of language deficits and recovery patterns in aphasia. Measurements extracted from diffusion-weighted (DW) images provide comprehensive in vivo measures of local microstructural properties of fiber pathways. In the current study, we compared microstructural properties of major white matter tracts implicated in language processing in each hemisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
139
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(166 citation statements)
references
References 84 publications
20
139
1
2
Order By: Relevance
“…More recent analyses of diffusion imaging data from aphasic individuals examining the functional significance of tract segments (rather than whole tracts) revealed a more complex picture, with portions of the dorsal AF and ventral ILF and IFOF associated with deficits in both language production and comprehension (Ivanova et al, 2016). As studies using diffusion imaging in brain-injured individuals evolve, the field will continue its examination of the role of fiber pathways in the processing of language.…”
Section: Diffusion Mrimentioning
confidence: 99%
See 3 more Smart Citations
“…More recent analyses of diffusion imaging data from aphasic individuals examining the functional significance of tract segments (rather than whole tracts) revealed a more complex picture, with portions of the dorsal AF and ventral ILF and IFOF associated with deficits in both language production and comprehension (Ivanova et al, 2016). As studies using diffusion imaging in brain-injured individuals evolve, the field will continue its examination of the role of fiber pathways in the processing of language.…”
Section: Diffusion Mrimentioning
confidence: 99%
“…Temporal tracts, such as the inferior longitudinal fasciculus (ILF), inferior frontal-occipital fasciculus (IFOF), and potentially also the uncinate fasciculus (UF) and middle longitudinal fasciculus, have been shown to be mainly involved in language comprehension (Ivanova et al, 2016;Kümmerer et al, 2013).…”
Section: Diffusion Mrimentioning
confidence: 99%
See 2 more Smart Citations
“…23) Previous DTI studies of aphasia caused by stroke reported that FA decreased in the left arcuate fasciculus and adjacent white matter fibers. 5,[27][28][29][30][31][32] In accordance with these previous findings, we set ROIs to include the arcuate fasciculus as defined in the skeletonized FA images (shown in Fig. 1).…”
Section: Image Processingmentioning
confidence: 99%